Propriedades biológicas e análise parcial do RNA1 codificador da replicase de isolados do Bean rugose mosaic virus - Barboza, Antonio Augusto Lazarini (2010)
Bean rugose mosaic (BRMV) is a member of the Comovirus genus. The virus genome consists of two molecules of single strand RNA, positive sense, called RNA1 and RNA2. BRMV has a restricted host range, causing systemic symptoms such as blistering and leaf deformation on beans. Soybean and bean plants showing characteristic symptoms of BRMV infection were collected in Paraná state. The isolates were maintained in 'Rio Tibagi' bean plants in greenhouse conditions. The virus purified preparation gave three peaks of absorbance readings that could be correlated to the comoviruses particle components. Indirect ELISA tests pointed to replication differential rates for each virus isolate that remained constant even after virus mixed infections. The RNA of both isolates was extracted and a protocol for semi-nested RT-PCR was used to amplify a RNA1 fragment of 700bp, that was cloned and sequenced. Comparisons of the nucleotide sequence with others from the Genbank showed 79% identity with RNA1 of Bean pod mottle virus. The identification of the RNA polymerase coded by BRMV RNA1 was confirmed through the GDD amino acid triad that is conserved in the RNA replicase of all positive sense viruses. The phylogenetic analysis allowed the classification of BRMV as a member of the Secoviridae family. BRMV could be situated next to BPMV, among other comoviruses infecting leguminosae plants. The sequence of the 3' RNA1 region of BRMV is deposited in the GenBank under the accession number GU205154 or gi284807373.